BEHAVIOR OF RARE EARTH ELEMENTS DURING LEACHING OF THE OCEANIC SEDIMENTS - Dubinin A.V.; Strekopytov S.V. (My University, 2001)
Oceanic sediments (volcanoterrigenous mud and hemipelagic and eupelagic clay) were leached by IM NH2OH · HCl + 25% CH3COOH at different solid/liquid ratios (from 1/800 to 1/20) to study the REE behavior in the leachates. At pH 2, no REE readsorption is observed. Kinetic experiments on leaching of the eupelagic clay (solid/liquid = 1/67) showed that equilibrium conditions for trivalent REEs are attained after four hours, while those for Ce are attained only after eight hours. This may indicate a tetravalent state of Ce in the oxidized pelagic sediments. Under equilibrium conditions, the introduction of trivalent REE during leaching leads to REE redistribution between IM NH2OH · HCl + 25% CH3COOH and the solid phase: added REEs disturb the equilibrium and cause the partial adsorption of these elements by the sediment. Under unequilibrium conditions (for Ce), no Ce redistribution was observed after Ce inroduction into the solution-sediment system. The experiments demonstrated that the amount of exchangeable REEs, which were determined in the leachate after four hours of treating the sediments with Chester's reagent at a solid/liquid ratio of 1/400, approximates the REE concentrations equilibrated with the solid phase. The REE concentrations are similar in repeated experiments with solid/liquid ratios from 1/800 to 1/100 and can be used to characterize the exchangeable portion of the bottom sediments. The contents of the major elements (Fe, Al, and P) in the leachate significantly depend on the conditions of the sediment treatment.